The ladybells Adenophora liliifolia (L.) Besser in forests near Kisielany (Siedlce Upland, E Poland) - Ciosek, Marek T. (Biodiversity: Research and Conservation, 2006)
The ladybells Adenophora liliifolia in Poland was found in only 8 sites after 1980, so it is now classified as critically endangered (E). Since 2001 the species has been strictly protected and enlisted in the Habitat Directive of the EU. In 1995 in Kisielany, northwest of Siedlce, a rich population of Adenophora liliifolia was found. This study was undertaken to characterize phytosociologically the patches with ladybells and to analyse the structure of this opulation. One hundred specimens were randomly selected for population analysis carried out in 2005. Measurements were done on live plants. Seven individual traits were measured or calculated, including plant height, number of flowers, leaf dimensions, etc. The analysed patches represent thermophilous oak forest Potentillo albae-Qurcetum. This is the largest Polish population of this species known so far, as it consists of several hundred flowering specimens. Adenophora liliifolia achieves greatest dimensions there and its mean height exceeds the data known from the literature. Quantitative contribution of ladybells to particular patches varies from “+” to “2” according to the Braun-Blanquet scale. The plant is accompanied by some protected species, like: Laserpitium latifolium, Cimicifuga europaea, Aquilegia vulgaris and Lilium martagon. A proposal has been submitted to protect the site as a nature reserve and the population will be studied further.